Pawn power and businessman Nikumatsu Okada in the Valley of Chancay - Rodríguez Pastor, Humberto (2017)
The text is partly the biography of a Japanese, Nikumatsu Okada, who was immigrated pawn of the first group of Japanese who came to Peru to work on coastal plantations 1899. Of pawn of Palpa hacienda, Chancay valley, became tambero, Yanacon and tenant farms and other businesses ; all in the same valley. He finished his presence in Peru because of deportation of Japanese-Peruvians to concentration camps in the US during the 2nd World War. It also includes part of the Japanese environment surrounding this businessman and was so much that today lasts the world nikkei in this valley.